Assessment of Hanoman’s Character Value (Indigenous) as a Counselor Competence for Industrial Revolution - Maya Tsuroya Alfadla; Putri Laras Trisnawati (Universitas Sebelas Maret, 2019)
Industrial Revolution 4.0 provides changes in digitalization and automation for various sectors in Indonesia. These changes have an impact on the Guidance and Counseling profession can be replaced by the role of robots and online counseling. This study will discuss how the Guidance and Counseling profession responds to the challenges by strengthening the competency of counselors through the analysis of Hanoman's character values as the character of indigenous counselors. Hanoman is a puppet character who has a face and body shape that resembles an ape but has a kind heart, is willing to sacrifice and responsibility. The developed Hanoman character is empathy, unconditional acceptance, dynamic, genuine, real self to be one step to strengthen the competence of indigenous counselors in the era of the industrial revolution. This strengthening aims to provide a unique Indonesian character in competing with the changes that occur.